Pengaruh Current Ratio, Debt to Equity Ratio, dan Net Profit Margin Terhadap Nilai Perusahaan Sektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Melissa Adhistiani Putri; Fathihani Fathihani (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This research examines the determinants of firm value in Food and Beverage companies listed on the Indonesia Stock Exchange (IDX) during 2019-2023. Using a quantitative causal approach, the study investigates the influence of Current Ratio (CR), Debt to Equity Ratio (DER), and Net Profit Margin (NPM) on firm value measured by Price to Book Value (PBV). The population comprises 12 Food and Beverage sector companies, with 60 samples obtained through purposive sampling. Panel data regression analysis using SPSS 26 reveals that DER significantly affects firm value (significance 0.000, regression coefficient 1.872), as does NPM (significance 0.010, coefficient 0.062), while CR shows no significant impact (significance 0.197). The F-test confirms that these three variables collectively have a significant effect on firm value (F-value 3.714, significance 0.017), demonstrating their combined ability to explain variations in firm value. These findings provide valuable insights for investors and management regarding investment decisions and financial strategy development in the Food and Beverage sector.